Nigerian university libraries in the digital world - any hope for survival? (2013)
The paper traced the growth of Nigerian university libraries from independence and highlighted the present deterioration of nearly all of them because of their neglect as a result of economic downturn of the country. The importance of digital libraries in Nigerian universities is discussed in the paper. The paper suggests ways and means by which Nigerian University libraries could improve upon the provision of their resources/services in the emerging digital environments to support effective learning, teaching and research